(3GdJMdjd GdfaSj GdacQj h GdSdhcjs - (3SQhQ(B, (3eMeOs ((3YeGfs (3ReRe fGTQhf hehRYhfs, 2023)
(3jgOa cJGH (B"(3GdJMdjd GdfaSj GdacQj hGdSdhcj(B" (3Edi JbOje QDjI TGedI dYGde Yde GdfaS GdEOGQj, eY GdJQcjR Ydi CgejI age GdSdhc GdEfSGfj aj HjFI GdYed dJMbjb GdcaGAI hGdEfJGLjI(B. (3jSJYQV GdcJGH HTcd efgLj GdeaGgje GdCSGSjI dYde GdfaS GdEOGQj, HOkAG ef JYQjaGJ GdYdhe GdSdhcjI hCgOGa GdJMdjd GdfaSj hakbG daQhjO(B. (3Ke jfJbd Edi GSJcTGa GdYfGUQ GdeDKQI Ydi GdSdhc aj ecGf GdYed, eKd GdTNUjI hGdbjGOI hGdGJUGd(B. (3ceG jJfGhd GdcJGH GSJQGJjLjGJ JMSjf GdCOGA GdhXjaj hQaY GdQhM GdeYfhjI dOi GdehXajf, eY GdJQcjR Ydi CgejI GdJhGUd GdaYGd hGdJhLjg GdSdje(B. (3HTcd YGe, jbOe GdcJGH EWGkQG fXQkjG hYedkjG dage GdSdhc GdEfSGfj aj GdefXeGJ, hjhaQ COhGJ hCSGdjH dJMSjf GdCOGA GdEOGQj(B.s
Keywords: (3GdbjGOI GdEOGQjI (B- (3GdJMdjd GdfaSj s; (3Yde GdfaS GdEOGQjs